FACTORS FORECASTING IN SELECTION OF ACCOUNTING SOFTWARE PACKAGE FOR NAWANAKHORN INDUSTRIAL ESTATE, PATHUM THANI PROVINCE - Aphiwatpisan, Nathapat (Journal of Liberal Arts and Management Science Kasetsart University, 2022)
The objectives of this research were to find factors forecasting in selection of accounting software package for Navanakorn Industrial Estate, Pathum Thani Province. Testing four variables; the function and capability, compatibility with the operating system and other program, vendor and after sales service, and price. The target population was accounting manager, accounting executives, or staff in accounting department. Data were gathered using the questionnaire and collected with ninety-nine questionnaires. Data were analyzed by using descriptive statistics such as the frequency, percentage, mean, and inferential statistic such as multiple regression analysis. Results indicated that the four majorities of forecasting in selection of accounting software package in descending order as follows: the function and capability is 68 percent, compatibility with the operating system and other program is 41.40 percent, vendor and after sales service is 27 percent, and price is 23.90 percent. The forecast efficiency is 45 percent.